A Molecular Reappraisal of Glomus Tumors and Related Pericytic Neoplasms With Emphasis on NOTCH-gene Fusions. (November 2020) - Agaram, Narasimhan P.; Zhang, Lei; Jungbluth, Achim A.; Dickson, Brendan C.; Antonescu, Cristina R.
Abstract : Glomus tumors (GTs), together with myofibroma (MF), myopericytoma (MP), and angioleiomyoma (AL) are classified as members of the perivascular myoid family of tumors. The reported genetic abnormalities across these neoplasms is dissimilar, arguing against a pathogenetically unified family; half of the GT showing NOTCH -gene fusions and a smaller subset BRAF V600E mutations, while PDGFRB mutations are noted in a subset of MF and MP. This study aimed to investigate the prevalence and specificity of NOTCH -gene fusions in a large group of GT and correlate with clinical features. BRAF-VE1 and PDGFRB immunoexpression was also investigated in this cohort. A total of 93 GT and 43 other pericytic lesions (11 MP, 13 MF, and 19 AL) were selected. All cases were tested by fluorescence in situ hybridization for NOTCH1-4 and MIR143 gene abnormalities and 6 cases were investigated by targeted RNA-sequencing. Fluorescence in situ hybridization revealed NOTCH -gene rearrangements in 50 (54%) GT, 2 MP (18%), and 2 AL (11%). NOTCH -rearrangements were present in 34 (68%) benign and 16 (32%) malignant GT. Fusion-positive benign GT were overwhelmingly seen in males with a predilection for extremities, while the malignant GT occurred mostly in viscera. Among the fusion-negative GT, 88% were benign, 9% uncertain malignant potential, and 2% malignant. Half of the fusion-negative GTs occurred in the finger/subungual region. In summary, rearrangements of NOTCH genes are seen in over half of GT, with NOTCH2 - MIR143 being the most common fusion (73%), while only a small subset of AL and MP share these abnormalities. The common subungual GT subset lack NOTCH -gene fusions suggesting an alternative pathogenesis. BRAF-VE1 was negative in all 37 cases studied, while strong PDGFRB staining was seen in 14 (21%) cases. Additional studies are needed to investigate the genetic alterations in the fusion-negative cases. Abstract : Supplemental Digital Content is available in the text.